The impact of frailty and multimorbidity on postoperative outcomes in older patients - Swarbrick, Claire (2025)
Older adults represent a growing proportion of the surgical population, with surgical interventions offering potential benefits including increased longevity and improved symptom management. However, older patients, particularly those living with frailty and multimorbidity, are at heightened risk of poor postoperative outcomes. Whilst evidence suggests that perioperative medicine services, especially those incorporating comprehensive geriatric assessment and optimisation, can improve these outcomes, the prevalence of frailty and multimorbidity amongst older surgical patients and their specific impact on postoperative outcomes have not been comprehensively described in a large, generalisable UK population.